Validation of dietary whey protein substrate challenge absorption test as an indicator of proteolysis - Kateryna Pierzynowska; Stefan Pierzynowski; Kamil Zaworski; Robert Gallotto; Meghana Sathe; Steven D. Freedman; Drucy Borowitz (PLoS ONE, 2025)
Introduction Current methods to measure the effectiveness of pancreatic protease activity are inadequate. We explored the measurement of peptide-derived amino acids following ingestion of dietary whey substrate as a sensitive test of exogenous protease activity in exocrine pancreatic insufficient (EPI) pigs. Methods We studied the activity of aspergillus protease given in combination with a novel lipase and fungal amylase, as well as commercially available pancrelipase in EPI pigs. After a high-fat diet plus a standardized dietary whey substrate, blood was withdrawn at intervals and was analyzed for amine groups using a modified ninhydrin reaction. Plasma peptide-derived amino acids were calculated. Results The AUC6 peptide-derived amino acid concentration was significantly increased in response to aspergillus protease as follows: 50 mg dose (137% increase; p = 0.05), 75 mg dose (154% increase; p = 0.008) compared to no enzyme. The AUC6 for peptide-derived amino acids after aspergillus protease increased by 133% for the 50 mg dose (p = 0.0044), by 171% for the 75 mg dose (p = 0.0002), and by 113% with 600 mg pancrelipase (p < 0.0001) when compared to no enzyme. Administration of 75 mg of aspergillus protease led to significantly higher peptide-derived amino acid AUC6 and Cmax when compared to 600 mg pancrelipase (p = 0.0419 and 0.0103, respectively). Conclusion In EPI pigs, measurement of peptide-derived amino acids following a meal with whey substrate differentiates the activity of aspergillus protease compared to no enzyme and the 75 mg dose was superior to pancrelipase. The evidence presented here in EPI pigs demonstrates that the whey substrate absorption challenge test reflects the proteolytic activity of different doses of exogenous pancreatic proteases.